Parental involvement, self-efficacy beliefs and subjective well-being of adolescents in Kuala Lumpur, Malaysia - Yap, Siew Ting (2015)
Many studies have highlighted the positive impact of paternal and maternal involvement on human developmental outcomes. Yet, differences in parental involvement across parent and child sex have been inadequately addressed in adolescents. Lately, subjective well-being (SWB) has become a new focus in psychology. However, little is known about the mechanisms underlying adolescent SWB. This cross-sectional research aimed to determine the differences of parental involvement across parent and adolescent sex and to elaborate the relationship between parental involvement and SWB by considering the potential mediation roles of academic self-efficacy (ASE), social self-efficacy (SSE), and emotional self-efficacy (ESE), and the potential moderation role of adolescent sex. A total of 722 adolescents from 14 public secondary schools in Kuala Lumpur, Malaysia participated in this study. The Father/Mother Involvement Scale (Finley & Schwartz, 2004), the Self-Efficacy Questionnaire for Children (Muris, 2001), the Positive and Negative Affect Schedule (Watson, Clark, & Tellegen, 1988), and the Students’ Life Satisfaction Scale (Huebner,1991) were the instruments used in this study. Results of the multigroup confirmatory factor analysis revealed that mothers had higher expressive, instrumental, and leisure/ companionship involvement than fathers. Besides, both fathers and mothers had higher expressive and instrumental involvement with their daughters than sons. Moreover, mothers had higher leisure/companionship involvement with their daughters than sons. Fathers showed no significant higher leisure/companionship involvement in either sons or daughters. As measurement invariance was established prior to the comparisons, the differences found may be substantive. The results of structural equation modeling demonstrated that ASE, SSE, and ESE uniquely mediated the relationships between parental involvement and positive affect. Besides, ASE was found to be the unique mediator in the relationships between parental involvement and life satisfaction. None of the proposed mediators mediated the relationships between parental involvement and negative affect. Moderation analyses showed that the relationship between paternal involvement and positive affect was significant for malesbut not females. Besides, the relationship between paternal involvement and ESE was stronger for males than females. Overall, this study provides valuable insights on Malaysian parents’ involvement in their adolescent children’s lives and highlights the roles of self-efficacy beliefs and adolescent sex in the relationship between parental involvement and adolescent SWB.